THE EFFECT OF FINANCIAL RATIOS IN PREDICTING PROFIT CHANGES IN MANUFACTURING COMPANIES LISTED ON THE STOCK EXCHANGE IN 2016 - 2020 - Naini Rizka Amalia; Bonita Prabasari; Adhi Widyakto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to prove how much influence the Current Ratio (CR), Debt to Equity Ratio (DER), and Net Profit Margin (NPM), Total Asset Turn Over (TATO), Return On Assets (ROA) simultaneously and partially affect the changes in profits of manufacturing companies in the consumption sector listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The population in this study are all manufacturing companies that produce consumer goods listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. Sample In this study, as many as 30 consumer manufacturing companies from various industries are listed on the Indonesia Stock Exchange. The type of data used is secondary data from the official website of the Indonesia Stock Exchange (IDX). The analysis technique uses multiple linear regression analysis . The partial results as a whole show Current Ratio (CR), Debt to Equity Ratio (DER), and Net Profit Margin (NPM), Total Asset Turn Over (TATO), Return On Assets (ROA) simultaneously have the same effect on Changes in Profit in consumption Manufacturing companies listed on the Indonesia Stock Exchange (IDX).